The Values of Local Wisdom in Dedeng: a Vocal Tradition of Malay Langkat Community - Koko Sujatmoko; Niza Ayuningtias (Politeknik Negeri Padang, 2017)
This research describes Dedeng as local vocal tradition of Malay Langkat community in the province of North Sumatra Indonesia along with its values and local wisdom embedded in it. The values, hopefuly can be used as guiding lines for young generation to build their character and live a better life based on values of vocal tradition Dedeng. Method: This research used qualitative research method. The data obtained through interviewing selected ethnic and religious groups communities and Focus Group Discussion (FGD). Finding: This research shows that Dedeng as local vocal tradition of Malay Langkat Community contains the values of respect to universe, environmental care, social interaction, respect for women and social mutual cooperation.